Preparation of Mesoporous Silica-Supported Chiral Amino Alcohols for the Enantioselective Addition of Diethylzinc to Aldehyde and Asymmetric Transfer Hydrogenation to Ketones - Sarkar, Shaheen M.; Md. Eaqub, Ali; Lutfor, M. R.; M. M., Yusoff
Optically active (−)-ephedrine, (−)-norephedrine, and (−)-prolinol were immobilized onto cubicmesoporousMCM-48 silica. The immobilized amino alcohols served as a heterogeneous chiral catalyst for the asymmetric addition of diethylzinc to aldehydes and transfer hydrogenation to ketones. The developed catalytic process yielded optically enriches secondary aromatic alcohols with 92–99% conversion and 70–82% enantioselectivity.